Dissociation mediates the association between intimate partner violence and posttraumatic stress among treatment-seeking incarcerated women. Issue 4 (7th August 2016) - DeCou, Christopher R.; Lynch, Shannon M.; Cole, Trevor T.; Kaplan, Stephanie P.
ABSTRACT: Objective : Women in prison experience high rates of interpersonal trauma as well as elevated rates of posttraumatic stress disorder (PTSD) relative to women in the general population. The present study examined the relationship between recent intimate partner violence (IPV), additional forms of lifetime trauma exposure, trait dissociation, and posttraumatic stress among a sample of incarcerated female survivors of IPV. Method : Participants were 186 treatment-seeking incarcerated women who reported experiences of IPV in the year prior to incarceration. Participants completed self-report measures of IPV, nonpartner-perpetrated lifetime trauma exposure, trait dissociation, and PTSD symptomatology. Associations among study variables were evaluated using sequential multiple regression. Results : Participants reported experiencing several forms of interpersonal trauma. More than half of respondents (i.e., 53%) fell beyond a conservative cutoff score on the PTSD Checklist–Civilian Version, indicating clinically significant symptoms of PTSD. Trait dissociation partially mediated the association between IPV and PTSD symptoms above and beyond history of nonpartner-perpetrated violence. Trait dissociation emerged as the strongest independent predictor of PTSD symptoms and explained approximately 15% of the variance in PTSD symptoms. Conclusion : This finding highlights the need for additional research concerning dissociation among women in prison and warrants consideration in future research and intervention efforts focused on trauma recovery among incarcerated women.